2020
DOI: 10.1002/tox.23040
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone loaded calcium alginate and polyvinyl alcohol carrier inhibits the 7,12‐dimethylbenz[a]anthracene‐induced hamster oral cancer via the down‐regulation of PI3K/AKT/mTOR signaling pathways

Abstract: Oral cancer is a multifactorial cancer that affects millions of peoples worldwide. The current exploration aimed to evaluate the mechanisms that thymoquinone nanoencapsulated carrier and its effects on 7,12‐Dimethylbenz[a]anthracene (DMBA) stimulated hamster buccal pouch cancer in Syrian hamster model. Nanocarrier was characterized by SEM, TEM, FTIR analysis. The incidence of tumor, and biochemicals makers was studied through standard methods. The mRNA expression level of inflammatory markers NF‐κBp50, NF‐κBp6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…In addition, TQ was suggested to express an antioxidant anti-inflammatory effect and enhance the detoxification processes [29,30]. Thymoquinone was reported to have different beneficial effects, such as; immunoregulatory [31], antioxidant [32], antidiabetic [33], anti-inflammatory [34], pain relieving [35], blood pressure regulatory [36], gastro protecting [37], renal protecting [38], and anti-malignancy [31,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TQ was suggested to express an antioxidant anti-inflammatory effect and enhance the detoxification processes [29,30]. Thymoquinone was reported to have different beneficial effects, such as; immunoregulatory [31], antioxidant [32], antidiabetic [33], anti-inflammatory [34], pain relieving [35], blood pressure regulatory [36], gastro protecting [37], renal protecting [38], and anti-malignancy [31,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Abdelfadil et al [101], in 2013, demonstrated that thymoquinone induces apoptosis by downregulating the p38MAPK pathway in chemically induced oral squamous cell carcinoma (T28). Pu et al [102], in 2021, showed that thymoquinone down-regulated the inflammatory and PI3K/AKT/mTOR signaling pathway in orally treated 7,12-dimethylbenz[a]anthracene (DMBA)stimulated hamster oral tumor. In addition to being effective as a treatment for cancer, thymoquinone is also effective as a chemopreventive agent.…”
Section: Thymoquinonementioning
confidence: 99%
“…However, the biopolymer inhibits the growth of oral cancer cells and has good antibacterial activity against Escherichia coli and Staphylococcus aureus and, thus, is suitable for topical wound care and periodontitis and oral cancer treatment (Chiaoprakobkij et al, 2020). TQ/Ca-alg-PVA, a product of loading with calcium alginate and polyvinyl alcohol onto thymoquinone (TQ), inhibits early-stage oral cancer in 7,12-Dimethylbenz [a]anthracene (DMBA) painted hamster by downregulating the expression of NF-κB p50/p65, and PI3K/ AKT/mTOR mRNA (Pu et al, 2021). In summary, natural polysaccharides can achieve precise treatment and reduce the drug resistance of oral cancer.…”
Section: Treatment Of a Combination Of Oral Soft And Hard Tissue Dise...mentioning
confidence: 99%